Antibiotic Resistance in Escherichia Coli Bacteria Isolated from Water Sources and Waste Disposal in Livestock Farms in East Lombok - Sa’diyah, Siti Nurus; Kholik, Kholik; Munawaroh, Muhammad; Aprianti, Aurira Thrisma Dwi; Rahmawati, Septiyana Eka; Riwu, Katty Hendriana Priscilia (Jurnal Sain Peternakan Indonesia, 2023)
Poor antimicrobial stewardship in livestock farms will lead to the emergence of bacterial resistance to antibiotics. Dug wells as a water source and waste disposal on livestock farms have a close distance, allowing transmission of Escherichia coli-resistant bacteria through soil absorption and fecal contamination. This study aims to isolate Escherichia coli from water sources and livestock waste disposal in East Lombok Regency and determine their sensitivity to several antibiotics. The type of this research is a descriptive cross-sectional survey using four water wells and four waste disposals with a criterion of < 10m range. Escherichia coli bacteria were isolated using culture techniques on Eosin Methylene Blue Agar, and identification was carried out using gram staining and biochemical tests. Determining sensitivity to antibiotics was performed using the Kirby-Bauer disk-diffusion method. The results showed that Escherichia coli bacteria have been isolated from water sources and waste disposal on livestock farms in East Lombok Regency. 100 % Escherichia coli isolates sensitive to Gentamicin, Ciprofloxacin, and Cefotaxime. 87.5% Escherichia coli isolates sensitive to Oxytetracycline, 12.5% ​​Escherichia coli isolates resistant to Oxytetracycline, 100% Escherichia coli isolates resistant to Penicillin G. Escherichia coli bacteria isolated from water sources and waste disposal at a livestock farm in East Lombok.